شروط مسكن الزوجية في قانون الأحوال الشخصية الأردني - الحنيطي، سناء جميل علي; آغا، خلوق ضيف الله محمد (جامعة مؤتة, 2018)
This study aims to clarify the conditions of the marital residence in the Islamic shari'a and the law of Jordanian personal circumstances no. 36 for year 2010. The researchers focused on these conditions and showed the more correct jurists ideas and then clarified the lawgiver purposes at every condition. The researchers in this study depend on the inductive approach and the descriptive approach. The most prominent results of this study are that the marital residence is the independent safe place where women move to it after her marriage, to settle it with her husband, asking housing and acceptable living, which is conditioned by: the independence and the presence of Furniture that leads to a decent living, and providing moral and material security. All of that achieving the purposes of shari'a which helps people to establish an ideal family at the society, and the most important of married life is sustainability and stability to maintain the religion and selves to building earth according to the law of God. The nature of study required to divide it into an introduction, three sections, and a conclusion.
تهدف هذه الدراسة إلى بيان شروط مسكن الزوجية في الشريعة الإسلامية وقانون الأحوال الشخصية الأردني رقم 36 لسنة 2010م، وقد ركز الباحثان على ذكر هذه الشروط وبيان الراجح من آراء الفقهاء فيها، ثم بيان مقصد الشارع في كل شرط منها، وقد اعتمد الباحثان في هذه الدراسة على المنهج الاستقرائي والمنهج التحليلي. وكان من أبرز نتائج هذه الدراسة أن مسكن الزوجية هو المكان المستقل الآمن الذي تنتقل إليه المرأة بعد زواجها، لتستقر فيه مع زوجها، طالبة فيه السكن والعيش الكريم، وأن شروط هذا المسكن هي: استقلاليته، ووجود الأثاث الذي يؤدي حاجة العيش الكريم فيه، وتوفير الأمن المادي والمعنوي، وتوافر هذه الشروط يحقق مقاصد الشرع من إنشاء الأسرة في المجتمع التي أهمها ديمومة الحياة الزوجية واستقرارها وتحقيق السكينة والطمأنينة للزوجين حفظا للنسل والدين والنفس بغية عمارة الأرض وفق شرع الله. وقد اقتضت طبيعة هذه الدراسة أن تقسم إلى مطلب تمهيدي وثلاثة مطالب وخاتمة، المطلب التمهيدي وفيه التعريف بمصطلحات البحث، والمطلب الأول عن استقلال الزوجة بمسكن خاص، والمطلب الثاني عن أثاث مسكن الزوجية وتوابعه، والمطلب الثالث في أمان مسكن الزوجية، وضمنا الخاتمة أهم النتائج
Keywords: الأردن -- القوانين والتشريعات -- قانون الأحوال الشخصية -- مسكن الزوجية -- مقاصد الشريعة -- الشريعة الإسلامية